The complete Sherlock Holmes. Volume I - Doyle, Arthur Conan, 1859-1930 (Signature classics (Union Square & Co. (Firm)), 2021)
Volume I: Here, in one volume, are the stories that transformed Sherlock Holmes into a household name: the fateful first meeting of Sherlock Holmes and Dr. Watson in A Study in Scarlet, the mysterious treasure of The Sign of the Four-- and more! --Publisher product page, 2024 edition, [with same ISBN].